The SEISICAT study: a pilot study assessing 1 efficacy and safety of spironolactone in cats with congestive heart failure secondary to cardiomyopathy - James, Rachel; Guillot, Emilie; Garelli-Paar, Catherine; Huxley, Jacqueline; Grassi, Vanessa; Cobb, Malcolm (Elsevier, 2018)
Introduction The pathophysiology of heart failure involves activation of several neurohormonal systems including the renin-angiotensin-aldosterone system. The mineralocorticoid receptor antagonist spironolactone has been shown to be beneficial in humans and dogs with heart failure. The objective of this pilot study was to investigate the efficacy and safety of spironolactone in cats with heart failure secondary to cardiomyopathy already treated with furosemide and an angiotensin-converting enzyme inhibitor.